Theoretical and methodological bases of Critical Bioethics facing the challenges of the Anthropocene - Cunha, Thiago Rocha da; Biscioni, Diego Nicolás (O Mundo da Saúde, 2023)
Critical Bioethics proposes a theoretical and methodological foundation starting from self-criticism about the field of bioethics itself, as well as the production of knowledge and technology as a whole, seeking to identify how ethical discourses are often used to hide agendas and interests that go contrary to what is expected from any bioethical production: the defense of health and life in its broadest aspect. This work presents an introduction, through an investigation of a theoretical and reflective nature, the main elements of Critical Bioethics, its insertion in the debate with other approaches in the area and its methods of methodological application. By considering some challenges related to the emergence of socio-environmental conflicts, and in dialogue with productions from studies on the Anthropocene and criticisms of the Capitalocene, the article concludes with an initial proposal for expanding its theoretical corpus.